Transformasi Media Sosial dalam Strategi Pemasaran: Analisis Bibliometrik - Dinni Kurnianti; Indah Adawiyah; Teguh Lingga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study delves into the evolution of social media within marketing strategies, employing a bibliometric approach. It delineates substantial shifts in consumer behavior and business methodologies consequent to the proliferation of social media platforms. The primary aim is to offer a nuanced comprehension of social media's role in contemporary marketing landscapes, alongside identifying prevalent trends and patterns within pertinent literature. Employing bibliometric analysis, the study scrutinizes relevant articles to unearth significant insights. Findings underscore a heightened scholarly interest in social media marketing strategies and unveil collaborative frameworks among researchers and institutions. The implications underscore the imperative of comprehending social media's role and influence in shaping modern marketing paradigms, accentuating its pertinence in contemporary business practices. This research is poised to furnish invaluable insights for marketing professionals and academics, empowering them to craft efficacious marketing strategies tailored to the digital era.